2019
DOI: 10.1590/s1677-5538.ibju.2018.0816
|View full text |Cite
|
Sign up to set email alerts
|

A prospective study assessing feasibility of performing percutaneous nephrolithotomy in chronic kidney disease patients - What factors affect the outcome?

Abstract: Objectives To primarily evaluate the functional outcomes of PCNL for bilateral renal calculi/calculi in solitary functioning kidney with Chronic Kidney Disease(CKD). To identify factors affecting the renal replacement therapy following PCNL.Materials and Methods Patients with bilateral renal calculi/calculi in solitary kidney and CKD (eGFR<60/s.creatinine>2) and Good Performance Status [Eastern Cooperative Oncology Group (ECOG): 0–2] were included in the study.Results A total of 60 patients with CKD who had bi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 24 publications
0
8
0
Order By: Relevance
“…This may be because impairment of renal function in the absence of significant perioperative complications appears to be minimal, transient and focal. Effect on renal function is influenced by preoperative renal status and presence of comorbidities such as diabetes mellitus and hypertension [15]. Violation of the renal parenchyma, high irrigation pressure, tract multiplicity, preoperative urine infection and postoperative bleeding are reported as attributes causing post-PNL AKI [2,16].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This may be because impairment of renal function in the absence of significant perioperative complications appears to be minimal, transient and focal. Effect on renal function is influenced by preoperative renal status and presence of comorbidities such as diabetes mellitus and hypertension [15]. Violation of the renal parenchyma, high irrigation pressure, tract multiplicity, preoperative urine infection and postoperative bleeding are reported as attributes causing post-PNL AKI [2,16].…”
Section: Discussionmentioning
confidence: 99%
“…Violation of the renal parenchyma, high irrigation pressure, tract multiplicity, preoperative urine infection and postoperative bleeding are reported as attributes causing post-PNL AKI [2,16]. However, subsequent improvement in renal function is seen in almost all renal units that are obstructed and infected [15,17]. Standardized definition of AKI was introduced to aid early detection and management and improve the overall patient outcomes [3].…”
Section: Discussionmentioning
confidence: 99%
“…GFR was utilized to gauge changes in renal function in 7 studies [2,10,12,[15][16][17][18]. Mean pre-operative, postoperative, and follow-up eGFR in these studies were observed to be 38.23, 47.23, and 45.33 mL/min/1.73 m 2 , respectively.…”
Section: Outcome Measuresmentioning
confidence: 99%
“…Chronic kidney disease (CKD) is emanating as a significant chronic health problem globally [1]. As per the Kidney Disease Outcomes Quality Initiative (K/DOQI) Advisory Board, CKD is defined as sustained kidney injury for >3 months with GFR <60 mL/min/1.73 m 2 [2]. In the USA, there were 6, 87,093 patients with end-stage re- nal disease at the end of 2015 [3].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation